Intranasal M2SR (M2-Deficient Single Replication) H3N2 Influenza Vaccine Provides Enhanced Mucosal and Serum Antibodies in Adults - Eiden, Joseph; Fierro, Carlos; Schwartz, Howard; Adams, Mark; Ellis, Kimberly J; Aitchison, Roger; Herber, Renee; Hatta, Yasuko; Marshall, David; Moser, Michael J; Belshe, Robert; Greenberg, Harry; et al. (The Journal of infectious diseases, 2022)
Abstract Background We previously demonstrated that an intranasal dose of 108 50% tissue culture infectious dose (TCID50) M2-deficient single replication (M2SR) influenza vaccine protected against highly drifted H3N2 influenza challenge in a subset of subjects who demonstrated ≥2-fold increase in microneutralization (MN) antibodies to Belgium2015 (the challenge strain) after vaccination. Here, we describe a phase 1b, observer-blinded, dose-escalation study demonstrating an increased proportion of responders with this signal of immune protection. Methods Serosusceptible subjects aged 18–49 years were randomized to receive 2 doses (108–109 TCID50) of M2SR or placebo administered 28 days apart. Clinical specimens were collected before and after each dose. The primary objective was to demonstrate safety of M2SR vaccines. Results The vaccine was well tolerated at all dose levels. Against Belgium2015, ≥ 2-fold increases in MN antibodies were noted among 40% (95% confidence interval [CI], 24.9%–56.7%) of subjects following a single 108 TCID50 M2SR dose and among 80.6% (95% CI, 61.4%–92.3%) after 109 dose (P < .001). A single 109 TCID50 dose of M2SR generated ≥4-fold hemagglutination inhibition antibody seroconversion against the vaccine strain in 71% (95% CI, 52.0%–85.8%) of recipients. Mucosal and cellular immune responses were also induced. Conclusions These results indicate that M2SR may provide substantial protection against infection with highly drifted strains of H3N2 influenza. Clinical Trials Registration NCT03999554. High dose of intranasal single replication M2SR influenza vaccine enhances mucosal and serum antibodies against drifted H3N2 influenza viruses. Serum microneutralization titer was shown to be a marker of protection against highly drifted H3N2 influenza in a previous challenge study. Lay Summary In recent years, influenza A H3N2 viruses have evolved into multiple cocirculating clades, resulting in low vaccine efficacy and highlighting the need for more effective influenza vaccines. In a previous challenge study, a single intranasal dose of the investigational vaccine M2SR demonstrated protection against a highly drifted H3N2 influenza challenge virus in a subset of vaccine recipients with a signature immune response. Increasing the dose of the M2SR vaccine in this phase1b study demonstrated a statistically significant increase in the proportion of subjects with the signature immune responses seen previously. The vaccine-induced antibodies were cross-reactive with a panel of drifted H3N2 viruses from 2007 to 2019. Additionally, M2SR generated a rise in serum hemagglutination inhibition antibody titer in 71% of subjects. In contrast, the H3N2 seroresponse rate for the licensed intranasal vaccine FluMist is 10% in seronegative adults. Moreover, M2SR elicited mucosal and cell-mediated immune responses. This study demonstrates that the intranasal M2SR generates a multifaceted immune response and has the potential to provide better efficacy against vaccine-matched strains and influenza drift variants reducing the need to update the vaccine on an annual basis. This is a noteworthy step in the development of a broadly protective influenza vaccine.